2017
DOI: 10.1073/pnas.1707794114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of directional pulling on mechanical protein degradation by ATP-dependent proteolytic machines

Abstract: AAA+ proteases and remodeling machines couple hydrolysis of ATP to mechanical unfolding and translocation of proteins following recognition of sequence tags called degrons. Here, we use singlemolecule optical trapping to determine the mechanochemistry of two AAA+ proteases, Escherichia coli ClpXP and ClpAP, as they unfold and translocate substrates containing multiple copies of the titin I27 domain during degradation initiated from the N terminus. Previous studies characterized degradation of related substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
87
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(98 citation statements)
references
References 38 publications
11
87
0
Order By: Relevance
“…Previous studies on degradation of water-soluble proteins by ClpXP and ClpAP have shown that the pulling forces generated by ATP hydrolysis act primarily on the local structure adjacent to a degradation marker 14,44,64 . Thus, degradation strongly depends on local conformational stability as well as unfolding cooperativity of the whole structure 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on degradation of water-soluble proteins by ClpXP and ClpAP have shown that the pulling forces generated by ATP hydrolysis act primarily on the local structure adjacent to a degradation marker 14,44,64 . Thus, degradation strongly depends on local conformational stability as well as unfolding cooperativity of the whole structure 59 .…”
Section: Discussionmentioning
confidence: 99%
“…We consider both possibilities unlikely as the distribution of translocation step lengths shows little dependence on trap force (Aubin-Tam et al, 2011;Maillard et al, 2011;Sen et al, 2013;Cordova et al, 2014;Olivares et al, 2017).…”
Section: Discrepancies Between Clpx Function and Sc/2r-model Predictionsmentioning
confidence: 99%
“…Single-chain ClpX ∆N was used to ensure subunits of the pseudohexamer do not dissociate during sample preparation. This enzyme has been used previously for many biochemical and single-molecule studies (Martin et al, 2005;2008a;2008b;Aubin-Tam et al, 2011;Maillard et al, 2011;Glynn et al, 2012;Sen et al, 2013;Stinson et al, 2013;Cordova et al, 2014;Iosefson et al, 2105a;2015b;Olivares et al, 2017;Rodriguez-Aliaga et al, 2016;Amor et al, 2019;Bell et al, 2018). We purified enzymes separately and incubated ClpX ∆N (4 µM pseudohexamer), ClpP (2 µM 14-mer), and ATPγS (5 mM) for five min before vitrification.…”
Section: Cryo-em Structuresmentioning
confidence: 99%
See 2 more Smart Citations